A comparison of eukaryotic viral 5'-leader sequences as enhancers of mRNA expression in vivo. - Gallie, D R (1987)
The 5'-untranslated leader sequences of several plant RNA viruses, and a portion of the 5'-leader of an animal retrovirus, were tested for their ability to enhance expression of contiguous open reading frames for chloramphenicol acetyltransferase (CAT) or beta-glucuronidase (GUS) in tobacco mesophyll protoplasts, Escherichia coli and oocytes of Xenopus laevis. Translation of capped or uncapped transcripts was substantially enhanced in almost all systems by the leader sequence of either the U1 or SPS strain of TMV. All leader sequences, except that of TYMV, stimulated expression of 5'-capped GUS mRNA with the native prokaryotic initiation codon context, in electroporated protoplasts. Only the TMV leaders enhanced translation of uncapped GUS mRNAs in protoplasts and increased expression of uncapped CAT mRNA in microinjected X. laevis oocytes. In oocytes, the TYMV leader sequence was inhibitory. In transformed E. coli, the TMV-U1 leader enhanced expression of both the native and eukaryotic context forms of GUS mRNA about 7.5-fold, despite the absence of a Shine-Dalgarno region in any of the transcripts. The absolute levels of GUS activity were all about 6-fold higher with mRNAs containing the native initiation codon context. In E. coli, the leaders of AlMV RNA4 and TYMV were moderately stimulatory whereas those of BMV RNA3, RSV and the SPS strain of TMV enhanced GUS expression by only 2- to 3-fold.